2012
DOI: 10.1155/2012/380905
|View full text |Cite
|
Sign up to set email alerts
|

An Intraoperative Case of Spontaneous Restoration of Circulation from Asystole: A Case of Lazarus Phenomenon

Abstract: This case report refers to a victim of intraoperative cardiac arrest, who restored spontaneous circulation despite of cessation of cardiopulmonary resuscitation (CPR). The victim, a 53-year-old man, was undergoing a surgical investigation and rehabilitation of a thigh hematoma. Two minutes after discontinuation of a 46 min CPR, a normotensive sinus node rhythm appeared at monitor. Despite of lack of an adequate explanation, the authors believe that the combination of the high total dose of adrenaline with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Although the biblical Lazarus rose from the dead without resuscitation attempts, there are no case reports of it occurring in someone who has died without CPR performed beforehand [9,33]. Almost all cases of autoresuscitation occurred after CPR following non-traumatic CA; there is only one report following traumatic CA [34] and four others associated with major haemorrhage [26,[35][36][37]. Therefore, it has been suggested that autoresuscitation is due to the medical interventions that were performed during resuscitation, but their effectiveness was delayed for some reason [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the biblical Lazarus rose from the dead without resuscitation attempts, there are no case reports of it occurring in someone who has died without CPR performed beforehand [9,33]. Almost all cases of autoresuscitation occurred after CPR following non-traumatic CA; there is only one report following traumatic CA [34] and four others associated with major haemorrhage [26,[35][36][37]. Therefore, it has been suggested that autoresuscitation is due to the medical interventions that were performed during resuscitation, but their effectiveness was delayed for some reason [38].…”
Section: Discussionmentioning
confidence: 99%
“…The Lazarus phenomenon has nothing to do with the trauma. 6 So far, two more cases of trauma have been reported. 7 8 What these cases have in common is that they were accompanied by severe chest injuries and PEAs were confirmed by cardiac arrest ECG rhythm.…”
Section: Discussionmentioning
confidence: 99%